2019
DOI: 10.1016/j.jand.2018.03.006
|View full text |Cite
|
Sign up to set email alerts
|

Caring for Transgender Patients and Clients: Nutrition-Related Clinical and Psychosocial Considerations

Abstract: The Continuing Professional Education (CPE) quiz for this article is available for free to Academy members through the MyCDRGo app (available for iOS and Android devices) and through www. jandonline.org (click on "CPE" in the menu and then "Academy Journal CPE Articles"). Log in with your Academy of Nutrition and Dietetics or Commission on Dietetic Registration username and password, click "Journal Article Quiz" on the next page, then click the "Additional Journal CPE quizzes" button to view a list of availabl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(18 citation statements)
references
References 37 publications
1
15
0
Order By: Relevance
“…As transgender individuals may opt to transition from one gender to the other using hormonal therapy and/or through gender-affirming surgeries, these practices may have a marked impact on their nutritional status, weight, and body habitus, which in turn, may impact the NFPE performed on these individuals [ 47 , 48 , 49 ]. Nonetheless, gender identification differences were not discussed during the expert focus group discussions, suggesting that this may be a relatively new area for the RDNs.…”
Section: Discussionmentioning
confidence: 99%
“…As transgender individuals may opt to transition from one gender to the other using hormonal therapy and/or through gender-affirming surgeries, these practices may have a marked impact on their nutritional status, weight, and body habitus, which in turn, may impact the NFPE performed on these individuals [ 47 , 48 , 49 ]. Nonetheless, gender identification differences were not discussed during the expert focus group discussions, suggesting that this may be a relatively new area for the RDNs.…”
Section: Discussionmentioning
confidence: 99%
“…In the United States, an estimated 0.6% of the adult population, or 1.4 million adults, identify as transgender [ 2 ]. No guidelines exist regarding nutrition assessment for transgender or gender non-conforming patients [ 3 ]. Transgender patients may opt to medically transition using hormone therapy and/or gender-affirming surgeries; these interventions may have a direct impact on nutrition related parameters such as weight status, body composition, lipid levels, blood pressure, and blood glucose levels [ 4 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…99 Regarding dietary considerations for trans individuals, the literature includes specific attention to eating disorders, 129 weight gain and chronic diseases. 136 The Health Risk Questionnaire above revealed that a lower percentage of TW reported eating five or more servings of vegetables or eating three or more servings of fruits per day, and a higher percentage of TW reported drinking caloric beverages, all compared with cis women and cis men. 137…”
Section: Part 3: Risks Associated With Gahtmentioning
confidence: 99%
“…99 Regarding dietary considerations for trans individuals, the literature includes specific attention to eating disorders, 129 weight gain and chronic diseases. 136 The Health Risk Questionnaire above revealed that a lower percentage of TW reported eating five or more servings of vegetables or eating three or more servings of fruits per day, and a higher percentage of TW reported drinking caloric beverages, all compared with cis women and cis men. 137 Given the lack of RCTs explaining the conflicting CV morbidity results among the available literature and the scarcity of data on older trans people, 91,93,104 the importance of ongoing large-scale prospective studies, such as STRONG, 101 the European Network for the Investigation of Gender Incongruence (ENIGI) 138 and GEnder Dysphoria Treatment in Sweden (GETS), 139 and optimal management of conventional risk factors (e.g.…”
Section: Cardiovascular Morbidity and Mortalitymentioning
confidence: 99%